Heirs in the Islamic, Anglo-Saxon and Continental European Legal Systems - Mulyadi, Kiking; Surasa, Ais; Ah. Fathonih; Rasyid, Fauzan Ali (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2025)
This study aims to compare the concept of inheritance in three different legal systems: Islamic law, Anglo-Saxon law, and Continental European law. The main objective of this study is to analyze the differences, similarities, and social and legal implications of these different inheritance systems. The methodology of this research involves a literature review and analysis of relevant laws and regulations regarding inheritance law in the three legal systems studied. Data is collected from reliable primary and secondary sources, including Islamic legal texts, relevant laws and court decisions in Anglo-Saxon law, as well as legal regulations and precedents in Continental European law. The findings of this study reveal that Islamic law regulates inheritance based on Sharia principles, which divide inheritance proportionally according to family relations and religious provisions. Anglo-Saxon law adheres to the principle of intestate succession, whereby property is distributed to heirs based on lineage and special rules in law. On the other hand, the Continental European legal system bases the distribution of inheritance on the concept of a broader lineage, encompassing more distant relatives as heirs. The social implications of these findings highlight differences in the way societies manage inheritance and inheritance rights, which can affect justice and harmony in the family. From a legal perspective, the implication is the comprehensive variation in the protection of inheritance rights and the legal process that applies in each legal system.